THE PHENOMENON OF USING LOCAL LANGUAGES ON ONLINE NEWS CHANNELS - Yawisah, Umi (Annual International Conferences on Language, Literature, and Media, 2023)
In this digital era, local language extinction, especially in Indonesia, should become a main concern in a linguistic field. The fact that the increasing number of people using Indonesian for their daily communication rather than their respective local languages indicates a paradigm shift towards local language amongst Indonesian society. This study aims at analyzing the extent to which local languages are used in writing articles or news in online news channels. By using a qualitative study, this paper seeks to find out the use of local language in headline news and its contents. The data were collected and documented from several news written in online media platform, then selected and classified by tabulating the relevant data before analyzing them comprehensively. The findings of this study reveals that the use of local language in online news channels occurs in the title and content of the news. Local languages are used because of the difficulty in finding the right equivalents and translations that are not familiar to many people. At the end of this paper, it is concluded that local languages must be preserved because the diversity of languages increases the creativity of one’s thinking.